1986
DOI: 10.1149/1.2108456
|View full text |Cite
|
Sign up to set email alerts
|

On the Role of Boric Acid in the Watts Bath

Abstract: Steady‐state polarization curves and cyclic voltammograms were obtained on Pt microelectrodes in various solutions in Ni ions. The data indicated that at a Pt surface in a solution of NiSO4 , H2 was deposited before the metallic Ni layer was laid down. In the Watts bath (containing NiSO4 , NiCl2 , and boric acid), the Ni layer was deposited before H2 was evolved. The presence of boric acid lowers the overvoltage for Ni deposition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0
1

Year Published

1987
1987
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(61 citation statements)
references
References 7 publications
2
58
0
1
Order By: Relevance
“…When a broader potential window is used (Figure 3a), the anodic peaks appear at ∼−0.2 V (A1) followed by the peak at ∼+0.3 V (A2) and ∼+0.75 V (A3), indicating the dissolution of β-Ni and Ni metal, and oxidation of Ni species (hydroxide/oxide) respectively. 31,32 This shows that β-Ni is primarily formed when a higher negative potential is applied (>−1.0 V vs Ag/AgCl) compared to α-Ni. 33 The oxidation of Ni species to hydroxide/oxide was observed by the formation of a black deposited layer.…”
Section: Resultsmentioning
confidence: 91%
“…When a broader potential window is used (Figure 3a), the anodic peaks appear at ∼−0.2 V (A1) followed by the peak at ∼+0.3 V (A2) and ∼+0.75 V (A3), indicating the dissolution of β-Ni and Ni metal, and oxidation of Ni species (hydroxide/oxide) respectively. 31,32 This shows that β-Ni is primarily formed when a higher negative potential is applied (>−1.0 V vs Ag/AgCl) compared to α-Ni. 33 The oxidation of Ni species to hydroxide/oxide was observed by the formation of a black deposited layer.…”
Section: Resultsmentioning
confidence: 91%
“…9 Tensile specimens also have characteristic caps, which are a result of plating over the e-beam developed features. These caps are quite isotropic, and somewhat resemble mushroom tops.…”
Section: Electroplatingmentioning
confidence: 99%
“…[20]. They suggested that H 3 BO 3 in the Watts bath acted not only as a pH buffer but also as a homogeneous catalyst by forming a complex with Ni ions to lower the overvoltage for nickel deposition [21]. Karwas et al also found that the addition of H 3 BO 3 to a Co-Zn plating bath increased nucleation density of the deposits, content of Zn in the deposited alloy, and current efficiency of the electrodeposition [22].…”
Section: Analysis Of the Zincating Processmentioning
confidence: 99%